Smart home implementation based on Internet and WiFi technology - Wenbo, Yan; Quanyu, Wang; Zhenwei, Gao (2015 34th Chinese Control Conference (CCC), 2015)
Smart home has become more and more popular in recent years. It aims at helping people manage the home appliance freely and build an autonomous environment in home or work area. This paper introduces a wireless solution based on Internet protocol to manage the smart home units easily. Based on this approach, we design a smart home system with the implementation of related software and hardware. People can use smart phones or tablets to control or monitor the home appliances both locally and remotely. We come up with the concept of Smart Units and Home Proxy. Low cost WiFi module is used to build Smart Units. The combination of remote server and home proxy is a new scheme for remote control in which XMPP is used. The remote server can act as a service provider and provide service for different homes and offices.